Gestão e inovação de parceria empresarial: o caso da Faculdade Independente do Nordeste - FAINOR - Santos, Itamar Figueredo dos (2013)
The dynamic and competitive markets, increasingly between organizations has stimulated a differentiated strategy that is already proving to be very efficient and innovative companies in the administrative, management by partnership. Given this scenario, the establishment of strategic partnerships emerged as an important means of achieving competitive advantage, processes and / or innovative services. The success of this procedure, however, requires the effective management of the partnership as a condition for its potential benefits are achieved. This study examined the organizational management and partnership and how it reverses in innovation and competitiveness for FAINOR, and for this, it was used as a research strategy case study. The main results showed that in most cases, the partnership between HEIs and businesses covenant limited to the allocation of students as interns and the granting of partial scholarships for employees of businesses and entities affiliated with religious covenant. Another aspect was also observed to identify the absence of policies to guide the process of forming partnerships, making the implementation and strengthening of existing ones and others that might take hold.